"Brāhmaṇa" as an honorific in "Indianized" mainland Southeast Asia: a linguistic approach. (February 2019) - Pain, Frédéric
Abstract: This article aims at demonstrating that the Old Khmer b/vraḥ originates from a syllabic depletion of the Sanskrit word brāhmaṇa through a monosyllabization process, a widespread diachronic phenomenon among the Mon-Khmer languages of Mainland Southeast Asia. The paper will also show that this term must have been originally used as an honorific for deities and, consequently, for royalty. It therefore respectfully disagrees with two other current hypotheses according to which b/vraḥ would be an autochthonous Mon-Khmer word or would originate in the Sanskrit/Pali word vara- "excellent, splendid, noble". After being borrowed from Sanskrit, the Old Khmer braḥ spread via a contact phenomenon: from Old Khmer to Old Siamese, from Old Siamese to Old Shan through the "Thai Continuum", and from Old Shan to Old Burmese. The implications of this paper are twofold: firstly, it will sketch out a pattern for the historical relationships between different peoples of Mainland Southeast Asia; then, it will propose a first phase of Indianization in Southeast Asia, namely a local reconnotation of Indo-Aryan terms according to autochthonous socio-political contingencies, and consequently bring a draft answer to the "Woltersian" question: what is the local connotation of Indo-Aryan terms?